Palm oil mill effluent metagenome for cellulose-degrading enzymes - Ben Belgacem, Farah Fadwa; Bellag, Qualid Abdelkader; Ahmad, Abdul Aziz; Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah (Haitham Qaralleh, 2017)
Abstract: Functional metagenomic approach incorporating metagenomic DNA library construction and high-throughput screening has proven to be a powerful tool for identifying novel biocatalysts (Wouters et al. 2014). Culture enrichment strategies are additional pre-screening methods employed to provide an attractive means of enhancing the screening hit rate. In this work metagenomic DNA libraries were generated from Malaysian palm oil mill effluent (POME) microorganisms. Three different samples, namely fresh, ambient-cooled and anaerobic POME microorganisms were inoculated in a medium under controlled temperature, light and pH conditions, and in the presence of carboxymethylcellulose (CMC) for short incubation time in order to allow growth of microorganisms with cellulose-degrading capabilities. Quantitative and qualitative metagenomic DNA tests indicate the presence of high number of microbes in anaerobic POME compared to other samples which guided us to use this particular sample in further experiments. Titer test also showed that the number of enriched-library clones is 5 to 7 times higher than non-enriched anaerobic POME. The use of such a combination of enrichment strategy with metagenomics greatly improves the screening process for biocatalysts.